Formation of the Digital Economy as a Factor in Increasing the Country's Economic Growth - Mazhidova Iroda Gayratovna (International Journal on Integrated Education, 2022)
Accelerating scientific and technological progress leads to the emergence and rapid spread of new information technologies in society - the so-called digitalization of society. The economic systems of many countries are in search of effective ways to use the achievements of digitalization of society for economic growth.